Immunomic identification of malaria antigens associated with protection in mice - Siau, Anthony (2020)
Efforts to develop vaccines against malaria represent a major research target. The observations that 1) sterile protection can be obtained when the host is exposed to live parasites and 2) the immunity against blood stage parasite is principally mediated by protective antibodies suggest that a protective vaccine is feasible. However, only a small number of proteins have been investigated so far and most of the Plasmodium proteome has yet to be explored. To date, only few immunodominant antigens have emerged for testing in clinical trials but no formulation has led to substantial protection in humans. The nature of parasite molecules associated with protection remains elusive. Here, immunomic screening of mice immune sera with different protection efficiencies against the whole parasite proteome allowed us to identify a large repertoire of antigens validated by screening a library expressing antigens. The calculation of weighted scores reflecting the likelihood of protection of each antigen using five predictive criteria derived from immunomic and proteomic data sets, highlighted a priority list of protective antigens. Altogether, the approach sheds light on conserved antigens across Plasmodium that are amenable to targeting by the host immune system upon merozoite invasion and blood stage development. Most of these antigens have preliminary protection data but have not been widely considered as candidate for vaccine trials, opening new perspectives that overcome the limited choice of immunodominant, poorly protective vaccines currently being the focus of malaria vaccine researches.